Dynamic control of tunneling conductance in ferroelectric tunnel junctions - Zou, Ya-Yi; Chew, Khian Hooi; Zhou, Yan (IOP Publishing, 2013)
We investigate the dynamic characteristics of electric polarization P(t) in a ferroelectric junction under ac applied voltage and stress, and calculate the frequency response and the cut-off frequency f0, which provides a reference for the upper limit of the working frequency. Our study might be significant for sensor and memory applications of nanodevices based on ferroelectric junctions. © 2013 Chinese Physical Society and IOP Publishing Ltd.